Analysis Of Financial Performance Due To Credit Restructuring Policy At Batam City BPR - Juli Darmayanthi; Puspita Rama Nopiana; Putu Rani Susanthi; Asih Purwana Sari (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This study aims to determine the difference in financial performance when implementing a credit restructuring policy with the enactment of POJK No. 11/POJK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy on the Impact of the Spread of COVID-19 during the COVID-19 pandemic and BPR financial performance is assessed based on SEOJK No. 11/SEOJK.03/2022 concerning the Assessment of the Health Level (TKS) of BPR and BPRS. The study population is Conventional Rural Credit Banks (BPR) in Batam City, Riau Islands whose financial ratio reports can be obtained through the Financial Services Authority (OJK) website, so that with the selection criteria, the research sample becomes 9 BPRs. This research method is a comparative quantitative method with an analysis technique using the Wilcoxon Test. The results of the study explain that banking financial performance based on NPL Semester I/2020 and NPL Semester I/2021 shows differences after the implementation of the credit restructuring policy during the COVID-19 pandemic.